2018 UK national guideline for the management of donovanosis. (September 2018) - O'Farrell, Nigel; Hoosen, Anwar; Kingston, Margaret
The objective of this guideline is to provide guidance for the diagnosis and management of donovanosis, a now rare sexually transmitted infection. This guidance is primarily for professionals working in UK Sexual Health services (although others may find it useful) and refers to the management of individuals presenting with possible symptoms of donovanosis who are over the age of 16. An updated literature review since the last Clinical Effectiveness Group (CEG) guideline produced for this condition in 2011 has shown few new developments. Most reports in the literature relate to cases of unusual presentations of the condition.